Comparative study of antibiotic adsorption capacity of three brands of blood culture bottles - Yuan, Siqi; Yang, Jinxue; Deng, Nan; Peng, Jiayi; Ma, Ling; Du, Shuaixian (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeTo compare the adsorption capacity of BacT/ALERT FA Plus aerobic, FN Plus anaerobic bottles, BD BACTEC Aerobic/F Plus, resin-free Lytic/10 Anaerobic/F bottles and VersaTREK Aerobic, Anaerobic bottles for antibiotics.MethodsThe clinically commonly used vancomycin, cefoperazone/sulbactam, imipenem and penicillin were investigated in the study. These antibiotics were mixed with standard strains and sterile horse blood at certain concentrations and inoculated into aerobic and anaerobic bottles of the three blood culture systems, then placed in the automated blood culture instrument. The positive detection rate and time to detection (TTD) of these three blood culture systems were recorded within five days in order to compare their detection and adsorption of antibiotics. Finally, one of the most detectable blood culture bottles were used on patients in the comprehensive intensive care unit (ICU) for one month and analyzed retrospectively in comparison with previous data.ResultsThe detection rates of the aerobic bottles were 25/35 (71.4%) for BacT/Alert FA Plus and BACTEC Aerobic/F Plus bottles, 12/35 (34.3%) for VersaTREK Aerobic bottles. The detection rates of the anaerobic bottles were 20/35 (57.1%) for BacT/Alert FN Plus bottles, 1/35 (2.9%) for VersaTREK Anaerobic bottles, and no positive bottles were detected in BD BACTEC Lytic/10 Anaerobic bottles. The TTD for the BacT/Alert FA Plus bottle (24.4 hours) was 5.1 hours shorter than the BD BACTEC Aerobic/F Plus bottle (29.5 hours) and 34.1 hours shorter than the VersaTREK Aerobic bottle (58.5 hours). In the ICU, the detection rates were 12.5% and 9.1% for BacT/ALERT medium and VersaTREK medium, respectively. For gram-negative bacteria, the TTD for BacT/ALERT medium and VersaTREK medium were 19.02 hours and 18.29 hours, respectively. For gram-positive bacteria, the TTD for BacT/ALERT medium and VersaTREK medium were 22.25 and 35.87 hours, respectively.ConclusionThe BacT/ALERT system has relative advantages in the detection rate, TTD, and antibiotic adsorption capacity, and can be used selectively in patients who have received antibiotic therapy. The use of BacT/ALERT medium resulted in a relative increase in detection rates, as well as in the type and number of strains detected compared to the VersaTREK medium previously used in the comprehensive ICU.